2020
DOI: 10.3389/fpsyt.2020.563761
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Changes in Paternal Perinatal Depression Profiles—Insights From the DREAM Study

Abstract: In contrast to the large body of research on maternal perinatal depression, paternal perinatal mental health has received little attention; and longitudinal studies on paternal perinatal depression, following (expectant) fathers over time, are exceedingly rare. This population-based study aimed to (1) estimate prevalence rates of perinatal depression symptoms among German (expectant) fathers, (2) identify differential profiles of perinatal depression in (expectant) fathers, (3) determine modifiable predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 56 publications
2
16
0
3
Order By: Relevance
“…Similarly, expectant fathers also appear to have an increased risk of depression in the perinatal period (13,21,22). While the prevalence rate of depression in men in the general population ranges between 3 and 6% (23)(24)(25), a meta-analysis found that the rate of paternal depression between the first trimester and 1 year postpartum was 10.4% (15), which was also observed recently in a sample of expectant fathers (26). There is also evidence for higher rates of anxiety disorders during pregnancy in both mothers and fathers (27).…”
Section: Introductionsupporting
confidence: 69%
“…Similarly, expectant fathers also appear to have an increased risk of depression in the perinatal period (13,21,22). While the prevalence rate of depression in men in the general population ranges between 3 and 6% (23)(24)(25), a meta-analysis found that the rate of paternal depression between the first trimester and 1 year postpartum was 10.4% (15), which was also observed recently in a sample of expectant fathers (26). There is also evidence for higher rates of anxiety disorders during pregnancy in both mothers and fathers (27).…”
Section: Introductionsupporting
confidence: 69%
“…The acceptable cut-off points for identifying potential perinatal depression range from 9–13, depending on the woman’s culture, language, or personal history of life [ 47 ]. It is commonly assumed that cut-off scores ≥10 indicate minor depression and ≥12 indicate major depression [ 48 ]. In Jaeschke et al [ 49 ], a score of 13 was adopted as the cut-off point, indicating a high level of depression.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there is a growing body of literature on paternal mental health in recent years, with a meta-analysis showing that around 8% of fathers have postpartum depression ( 48 ). In a recent large study of fathers, several depression profiles emerged with substantial stability from pregnancy to 2 months postpartum, although the depression levels decreased in the perinatal period ( 49 ). Another meta-analysis showed similar maternal and paternal depression effects on parenting behavior where depressed parents express less positive and more negative behaviors toward their children ( 50 ).…”
Section: Introductionmentioning
confidence: 99%